19‐4: Ultra‐Long‐Life Deep‐Blue OLED Device Achieved by Controlling the Carrier Recombination Site. Issue 1 (28th June 2021) - Ishimoto, Takuya; Hashimoto, Naoaki; Nomura, Shiho; Okuyama, Takumu; Nowatari, Hiromi; Suzuki, Tsunenori; Seo, Satoshi; Yamazaki, Shunpei
Abstract : The durability of a deep‐blue OLED device has been successfully improved by controlling the shift of the carrier recombination‐site during driving. This method can effectively suppress initial degradation and achieved an ultralong‐life device with an LT95 exceeding 800 h at a current density of 50 mA/cm 2 .